Imaging characteristics of wingless pathway subgroup medulloblastomas: results from the German HIT/SIOP-trial cohort - Quenzer, Annika; Pfister, Stefan; Sturm, Dominik (American journal of neuroradiology, 2019)
BACKGROUND AND PURPOSE: In addition to the 4 histopathologically defined entities of medulloblastoma, 4 distinct genetically defined subgroups have been included in the World Health Organization classification of 2016. The smallest subgroup is the medulloblastoma with activated wingless pathway. The goal of this study was to identify a typical MR imaging morphology in a larger number of pediatric patients with wingless pathway medulloblastoma. - MATERIALS AND METHODS: From January 2001 to October 2017, of 75 patients with histologically confirmed and molecularly subgrouped wingless pathway medulloblastomas recruited to the German Pediatric Brain Tumor (HIT) trials, 38 patients (median age, 12.8 ± 4.6 years at diagnosis; 24 [63.2%] female) had preoperative imaging that passed the entry criteria for this study. Images were rated by the local standardized imaging criteria of the National Reference Center of Neuroradiology. Additionally, a modified laterality score was used to determine tumor localization and extension. - RESULTS: Twenty-eight of 38 (73.7%) were primary midline tumors but with a lateral tendency in 39.3%. One extensively eccentric midline tumor was rated by the laterality score as in an off-midline position. Five tumors were found in the cerebellopontine angle; 3, in the deep white matter; and 2, in a cerebellar hemisphere. Leptomeningeal dissemination was rare (11.5%). In 60.5%, intratumoral blood-degradation products were found, and 26.3% showed cysts with blood contents. - CONCLUSIONS: According to our observations, wingless pathway medulloblastomas are not preferentially off-midline tumors as postulated in previous studies with smaller wingless pathway medulloblastoma cohorts. Dense intratumoral blood-degradation products and cysts with blood contents are frequently found and might help to differentiate wingless pathway medulloblastoma from other medulloblastoma subtypes.
Gesehen am 27.04.2020